Sensory, functional characteristics and in vitro digestibility of snacks supplemented with non‐traditional ingredient raw and processed fenugreek. (12th November 2021) - Wani, Sajad Ahmad; Alwahibi, Mona S.; Elshikh, Mohamed S.; Abdel Gawwad, Mohamed R.; Ali, Mohammad Ajmal; Alhaji, Jwaher Haji; Naik, Haroon Rashid; Kumar, Pradyuman
Summary: Fenugreek seeds were germinated, soaked and roasted and were evaluated for nutritional properties. Raw and processed fenugreek seeds were used to develop snack product. Snacks were examined for the sensorial, functional, antinutritional properties and in vitro digestibility. Using sensory analysis, 5% level of substitution of raw and processed fenugreek was accepted for the development of extruded snacks. Lateral expansion was highest for snacks prepared from processed fenugreek (163.0% to 206.1%) than raw fenugreek (162.5 to 168.7%), and vice versa for bulk density. The antioxidant activity and total phenolic content were highest for snacks prepared from germinated fenugreek (7.30% to 9.87% and 1.352 to 3.561 mg GAE g −1 of sample) and lowest for snacks prepared from raw fenugreek (6.68% to 7.03% and 1.29 to 2.76 mg GAE g −1 of sample). Not only extrusion but also processing such as soaking, roasting and germination reduced the antinutritional content of the snack product. Both in vitro digestibilities increased with extrusion cooking. In vitro digestibility was also found to be higher in snacks prepared from processed fenugreek than raw fenugreek. Therefore, development of such functional foods using processed fenugreek would raise the consumer demand and benefit the population by increasing the health status. Abstract : Development of healthy fenugreek based functional food with good consumer acceptability. Extrusion has improved in vitro digestibility and also reduced antinutritionals. Higher antioxidants in snacks are important as far as human health is concerned.